A Small Cluster Approach for the Electronic Density of States in Amorphous Germanium - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
The electronic density of states for very small clusters of amorphous germanium is calculated by using bonding orbitals. In this context, the Born model is considered as well as Pauling-type hybridized sp3 orbitals.